2014
DOI: 10.1007/s10964-014-0090-2
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and Overgeneral Autobiographical Memory in Adolescents: An Integration of Cognitive Vulnerabilities to Depression

Abstract: During adolescence, rates of depression dramatically increase and girls become twice as likely as boys to develop depression. Research suggests that overgeneral autobiographical memory and rumination are vulnerability factors for depressive symptoms in adolescence that may be triggered by stressful life events. The current longitudinal study included 160 early adolescents (Mage = 12.44 years, 60.0 % African American, 40.0 % Caucasian, and 56.2 % female). At baseline, adolescents completed measures of current d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 56 publications
11
55
2
1
Order By: Relevance
“…These reports and findings are also confirmed by Aglan et al . and Hamlat et al . On the other hand, Rosenbach and Renneberg claim that high sensitivity to rejection, which is a consequence of numerous traumatic experiences in relationships with the closest family in childhood, predisposes to dysfunctions of AM.…”
Section: Function Of the Hypothalamic–pituitary–adrenal Axissupporting
confidence: 74%
See 2 more Smart Citations
“…These reports and findings are also confirmed by Aglan et al . and Hamlat et al . On the other hand, Rosenbach and Renneberg claim that high sensitivity to rejection, which is a consequence of numerous traumatic experiences in relationships with the closest family in childhood, predisposes to dysfunctions of AM.…”
Section: Function Of the Hypothalamic–pituitary–adrenal Axissupporting
confidence: 74%
“…Overgeneral memories refer to fairly often repeated situations (‘I go to church every Sunday’) or to situations that last longer than 1 day (‘I was in second grade of middle school last year’) . In response to an emerging stimulus, patients with symptoms of depression recollect overgeneral memories more often than the specific ones . This concerns mainly negative memories.…”
Section: Am In Recurrent Depressive Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with previous research (Gibbs & Rude, 2004; Hamlat et al, 2014). Difficulty in retrieving specific autobiographical memories is one of the features of depression, and individuals with lower levels of autobiographical memory specificity had a higher level of depression (Hermans et al, 2008).…”
Section: Discussionsupporting
confidence: 94%
“…What studies have differed on is whether individuals with other psychiatric diagnoses also show similar patterns of OGM, raising questions over whether these are distinct features of depression. Several studies (Kleim & Ehlers, ; Rawal & Rice, ; Sumner et al., ) have found that fewer specific memories predict subsequent episodes of depression longitudinally (after controlling for baseline depressive symptoms) especially in girls (Hamlat et al., ) and in those with previous depressive episodes (Kleim & Ehlers, ). However, not all studies have been promising (Crane et al., ).…”
Section: A Review Of Information‐processing Factors Involved In Childmentioning
confidence: 99%